Transarterial Chemoembolization Followed by Radiotherapy Versus Sandwich Treatment for Unresectable or Ablative Hepatocellular Carcinoma. (23rd December 2020) - Lin, Haimin; Wu, Huiyong; Cong, Ning; Liu, Bo; Liu, Chengxin; Han, Dali
Objective: Our objective is to assess whether the outcome of intrahepatic unresectable or ablative hepatocellular carcinoma (HCC) could be improved by supplemental transarterial chemoembolization (TACE) following initial treatment of TACE with 3-dimensional conformal radiotherapy (3DCRT), compared to TACE followed by 3DCRT alone. Methods: We retrospectively analyzed intrahepatic unresectable or ablative HCC patients who underwent TACE, followed by 3DCRT with or without additional TACE, from June 2010 to December 2016 at our institution. Survival was assessed using the Kaplan-Meier method and compared with the log-rank test. Cox regression analyses were used to identify factors that influenced prognosis. Toxicity profiles were evaluated using CTCAE 4.0. Results: 27 patients received TACE with 3DCRT (TR group) and 11 received additional TACE following TACE and 3DCRT (sandwich group), respectively. The median intrahepatic progression-free survival (IPFS), progression-free survival (PFS), and overall survival (OS) in the TR group and sandwich group were 5.4 months vs. 17 months (P = 0.018), 5.4 months vs. 17 months (P = 0.008), and 13.5 months vs. 29.2 months (P = 0.011), respectively. Multivariate Cox regression demonstrated that TACE followed by radiotherapy alone had a shorter IPFS (HR: 2.516, 95% CI (1.136-5.570), P = 0.023) and PFS (HR: 2.637, 95% CI (1.182-5.880), P = 0.018) compared with the sandwich treatment. Hepatitis B virus reactivation occurred in 1 patient in the sandwich group. Myleosuppresion was considered a grade 3/4 adverse event. Conclusion: Unresectable or ablative HCC patients possibly benefit from the combination of TACE and 3DCRT followed by additional TACE therapy, compared with TACE followed by 3DCRT alone.